Moral Judgments on Short-Term Sexual Behaviors among Chinese College Students: Exploring the Roles of Gender and Physical Attractiveness - Xiao, Qianguo; Li, Aijuan; Zhu, Yi (Frontiers in Psychology, 2017)
This study primarily investigated the effects of gender and physical attractiveness on moral judgments on three typical kinds of short-term sexual behaviors (short-term fling, one-night stand, and hookup) in the Chinese culture context. A total of 120 university student subjects were presented with a series of stereotypically physically attractive (versus physically unattractive) photos before they rated the extent to which each of the three short-term sexual behaviors are morally acceptable. The results showed that male students judged all three behaviors to be more morally acceptable than female students did. Further analyses showed that this gender difference was moderated by the level of physical attractiveness. Under the high attractiveness condition, short-term flings and hookups were judged more morally acceptable by male students than by female students, but this gender difference was not significant under the low attractiveness condition. However, with regard to one-night stands, the data showed that male students judged this type of behavior to be more morally acceptable than did female students under the low attractiveness condition, while this gender difference was not significant under the high attractiveness condition. Thus, these findings further our understanding of how Chinese young people view different types of short-term sexual behaviors, and provide novel evidence regarding how physical attractiveness influences people’s moral judgments on short-term sexual behaviors.